Recombinant IL-7/HGFβ hybrid cytokine enhances T cell recovery in mice following allogeneic bone marrow transplantation. - Laijun Lai (Public Library of Science (PLoS), 2013)
T cell immunodeficiency is a major complication of bone marrow (BM) transplantation (BMT). Therefore, approaches to enhance T cell reconstitution after BMT are required. We have purified a hybrid cytokine, consisting of IL-7 and the β-chain of hepatocyte growth factor (HGFβ) (IL-7/HGFβ), from a unique long-term BM culture system. We have cloned and expressed the IL-7/HGFβ gene in which the IL-7 and HGFβ genes are connected by a flexible linker to generate rIL-7/HGFβ protein. Here, we show that rIL-7/HGFβ treatment enhances thymopoiesis after allogeneic BMT. Although rIL-7 treatment also enhances the number of thymocytes, rIL-7/HGFβ hybrid cytokine was more effective than was rIL-7 and the mechanisms by which rIL-7 and rIL-7/HGFβ increase the numbers of thymocytes are different. rIL-7 enhances the survival of double negative (DN), CD4 and CD8 single positive (SP) thymocytes. In contrast, rIL-7/HGFβ enhances the proliferation of the DN, SP thymocytes, as well as the survival of CD4 and CD8 double positive (DP) thymocytes. rIL-7/HGFβ treatment also increases the numbers of early thymocyte progenitors (ETPs) and thymic epithelial cells (TECs). The enhanced thymic reconstitution in the rIL-7/HGFβ-treated allogeneic BMT recipients results in increased number and functional activities of peripheral T cells. Graft-versus-host-disease (GVHD) is not induced in the rIL-7/HGFβ-treated BMT mice. Therefore, rIL-7/HGFβ may offer a new tool for the prevention and/or treatment of T cell immunodeficiency following BMT.